2019
DOI: 10.1155/2019/5819805
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity of Visible Light-Activated TiO2 Thin Films with Low Level of Fe Doping

Abstract: Development of effective antibacterial visible light-activated photocatalytic materials in industries including wastewater treatment and food industry has attracted increasing attention. In this work, Fe-doped TiO2 thin films with different doping levels on a glass substrate were prepared by the sol-gel dip-coating method. The as-prepared films were characterized by Raman spectroscopy, X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), and atomic force microscope (AFM). Raman spectroscopy and XRD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 44 publications
1
12
0
Order By: Relevance
“…After visible light irradiated for 120 min, the OD600 value of Fe-TiO2/kaolinite is much lower than TiO2/kaolinite and TiO2, where arise to 0.01 and 0.23, respectively. It may be an indication that the formation of photogenerated electronhole pairs on the surface of Fe-TiO2/kaolinite is easier to occur than TiO2 when absorbing visible light because it has a smaller band gap as a result of the mixing of the Fe 2p with Ti 2p orbitals [16][17][18]. These results are consistent with the absorption spectra.…”
Section: Photocatalytic Activity As Antibacterial Escherichia Colisupporting
confidence: 79%
See 2 more Smart Citations
“…After visible light irradiated for 120 min, the OD600 value of Fe-TiO2/kaolinite is much lower than TiO2/kaolinite and TiO2, where arise to 0.01 and 0.23, respectively. It may be an indication that the formation of photogenerated electronhole pairs on the surface of Fe-TiO2/kaolinite is easier to occur than TiO2 when absorbing visible light because it has a smaller band gap as a result of the mixing of the Fe 2p with Ti 2p orbitals [16][17][18]. These results are consistent with the absorption spectra.…”
Section: Photocatalytic Activity As Antibacterial Escherichia Colisupporting
confidence: 79%
“…The absorption peak at 602 cm −1 and 786 cm −1 observed on the spectrum of TiO2 corresponded to the stretching vibrations of Ti−O−Ti [15,16,26,27]. It has been observed that the addition of Fe into TiO2 matrix cause a shift of this band position to 586 cm −1 and 774 cm −1 for the Fe-doped TiO2, it is considered as a sign of existence structure defect [27].…”
Section: ( ) (mentioning
confidence: 99%
See 1 more Smart Citation
“…The photocatalytic properties of titanium oxide are well known and broadly described; in presence of water and a close range of UV light (λ ≤ 387 nm) it generates reactive forms of oxygen preventing the development of pathogens and the formation of biofilm [ 31 ]. Meng et al [ 32 ] highlight at the same time that the antibacterial action may be intensified by the modification of TiO 2 itself with such metals as Fe, thus increasing the activating spectrum to the visible light range. The effectiveness of the antimicrobial action is correlated by the authors with the weight content of titanium oxide in relation to PMMA [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Meng et al [ 32 ] highlight at the same time that the antibacterial action may be intensified by the modification of TiO 2 itself with such metals as Fe, thus increasing the activating spectrum to the visible light range. The effectiveness of the antimicrobial action is correlated by the authors with the weight content of titanium oxide in relation to PMMA [ 32 ]. Cheng [ 33 ] provides the weight content of 5% as optimum in terms of microbiology.…”
Section: Discussionmentioning
confidence: 99%